Characterization of the Multi-Drug Resistance Gene cfr in Methicillin-Resistant Staphylococcus aureus (MRSA) Strains Isolated From Animals and Humans in China - Li, Shu-Min; Zhou, Yu-Feng; Li, Liang; Fang, Liang-Xing; Duan, Jia-Hong; Liu, Fan-Rui; Liang, Hua-Qing; Wu, Yu-Ting; Gu, Wei-Qi; Liao, Xiao-Ping; Sun, Jian; Xiong, Yan-Qiong; et al. (Frontiers in Microbiology, 2018)
We investigated cfr-positive and -negative MRSA strains isolated from animals and humans in different geographical areas of China, from 2011 to 2016. Twenty cfr-positive strains (15.6%) were identified from 128 MRSA strains including 17 from food animals and 3 from humans. The resistance rates and prevalence of the tested antibiotic resistance genes (ARGs) in the cfr-positive MRSA isolates were higher than that in the cfr-negative MRSA isolates. All cfr-positive MRSA isolates were co-carrying fexA and ermC, and had significantly higher optrA incidence rate vs. the cfr-negative isolates (P<0.05). In addition, MLST assays showed that ST9 and spa-type t899 were the most prevalent ST and spa types in the study strains. However, all of the 20 cfr-positive and 10 randomly selected cfr-negative MRSA isolates were clonally unrelated as determined by PFGE analyses. Importantly, the cfr gene was successfully transferred to a recipient S. aureus strain RN4220 from 13 of the 20 cfr-positive MRSA isolates by electroporation. Among these 13 cfr-positive MRSA isolates, two different genetic contexts surrounding cfr were determined and each was associated with one type of cfr-carrying plasmids. Of note, the predominant genetic context of cfr was found to be a Tn558 variant and locate on large plasmids (~ 50 kb) co-harboring fexA in 11 of the 13 MRSA isolates. Furthermore, the cfr gene was also identified on small plasmids (~ 7.1 kb) that co-carried ermC in 2 of the 13 MRSA isolates. Our results demonstrated a high occurrence of multi-drug resistance in cfr-positive MRSA isolates, and the spread of cfr might be attributed to horizontal dissemination of similar cfr-carrying transposons and plasmids.